CLOSING THE LOOP BETWEEN PRIMARY CARE AND COMMUNITY SERVICE DELIVERY SYSTEMS FOR OLDER ADULTS. (11th November 2018) - Jurkowski, E; Smaga, S; Heitkamp, R; Nelson, M
Abstract: The OACCI/Closing the Loop initiative was an attempt to bridge primary care and community based services. This approach utilized a social work based approach to providing community care. The main objective was to provide seamless care to high risk older adults seen in primary care practice in a rural Midwest community and reduce hospitalizations and Emergency Department visits of older adults, or 30 day readmissions post hospital discharge. Outcomes were initially intended to be measured at 1 month, 3 months and 1 year intervals through chart reviews. Chart reviews provided data on demographics, health status, and diagnosis and health outcomes. Data was collected as close as possible to these time intervals, and for a one year period following the initial assessment. Outcomes included positive changes in bloodwork and chemistry, and lowered readmissions to the hospital or emergency room. Overall, a larger percentage of refusals of service initially was found. The community services partner integrated the process of contacting a Case Manager from the Community Based Assessment Team to meet with the patient during their primary care appointment. This strategy has increased the number of consumers accepting services. The primary care partner co-located at a teaching clinic integrated a script to help sell the process to consumers. The script used by Residents and treating physicians was found to help increase the number of consumers accepting services. This intervention's early outcomes identified the need to create policy and programmatic changes which will impact both primary care and community based service delivery systems.